2006
DOI: 10.1152/ajplung.00207.2006
|View full text |Cite
|
Sign up to set email alerts
|

Zinc modulates cytokine-induced lung epithelial cell barrier permeability

Abstract: Apoptosis plays a causative role in acute lung injury in part due to epithelial cell loss. We recently reported that zinc protects the lung epithelium during inflammatory stress whereas depletion of intracellular zinc enhances extrinsic apoptosis. In this investigation, we evaluated the relationship between zinc, caspase-3, and cell-to-cell contact via proteins that form the adherens junction complex. Cell adhesion proteins are directly responsible for formation of the mechanical barrier of the lung epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 36 publications
(34 reference statements)
3
78
0
Order By: Relevance
“…Indeed, zinc supplementation to Crohn's disease patients during clinical remission reduced intestinal permeability [12]. A similar role on epithelial barrier, and thereby permeability, was described for Zn 2þ in lung bacterial infection [43]. Importantly, a direct effect of ZnR/GPR39 on the epithelial barrier is also supported by the faster renewal of the epithelial surface layer along the mucosa with crypt reorganization and increased proliferation rate of epithelial cells in WT compared with ZnR/GPR39 KO mice.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, zinc supplementation to Crohn's disease patients during clinical remission reduced intestinal permeability [12]. A similar role on epithelial barrier, and thereby permeability, was described for Zn 2þ in lung bacterial infection [43]. Importantly, a direct effect of ZnR/GPR39 on the epithelial barrier is also supported by the faster renewal of the epithelial surface layer along the mucosa with crypt reorganization and increased proliferation rate of epithelial cells in WT compared with ZnR/GPR39 KO mice.…”
Section: Discussionmentioning
confidence: 67%
“…The blockage of the nuclear translocation of NF-B, as well as the suppression of IL-1␤ expression, might reduce the induction of inflammatory cytokines and neutrophil alveolar infiltration in BLM-treated, RKT-administered mice. The numbers of apoptotic AECs have been positively correlated with the levels of alveolar capillary barrier dysfunction, enhanced lung permeability, and subsequent lung scarring (3,30). We showed here that the administration of RKT reduced the apoptosis of AECs in BLM-treated mice.…”
Section: Discussionsupporting
confidence: 50%
“…They observed that zinc deprivation combined with proinflammatory cytokines accelerated caspase-3 activation, leading to increased paracellular leak across monolayers of lung epithelial cultures. Zinc also plays a role in the regulation of cellular glutathione (29) and protects cell membranes from oxidative damage (30). This is particularly intriguing, as we have published extensively on the role of oxidant stress and glutathione depletion in experimental models of chronic alcohol ingestion and in human subjects with alcohol abuse (5,7,(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%